1998
DOI: 10.1039/a800999f
|View full text |Cite
|
Sign up to set email alerts
|

Origin of stereofacial selectivity in electrophilic additions to methylenecyclohexanes and methylenedioxanes. A theoretical and experimental study

Abstract: Addition reaction studies and ab initio calculations on methylenecyclohexane and 5-methylene-1,3dioxane systems suggest that two electronic factors contribute to the stereoselectivity of epoxidation and diimide reduction. These are respectively the spatial anisotropy of the HOMO with respect to the two faces of the double bond, common to both molecules, which is likely to be responsible for the overall axial stereofacial selectivity exhibited, and a similar anisotropy in the electrostatic potential field of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…For dioxane 6g , diimide reduction occurred with excellent trans selectivity, in accord with the literature 18. The selectivity was attributed to the anisotropy effect induced by the oxygen atoms, as previously proposed.…”
Section: Resultssupporting
confidence: 89%
“…For dioxane 6g , diimide reduction occurred with excellent trans selectivity, in accord with the literature 18. The selectivity was attributed to the anisotropy effect induced by the oxygen atoms, as previously proposed.…”
Section: Resultssupporting
confidence: 89%
“…For single step electrophilic additions to C᎐C double-bonds, we have already shown that the stereochemistry is profoundly influenced by the hyperconjugative interactions between the π system and a C᎐X bond situated β with respect to it. 1 We have here demonstrated that, for two step additions of positive halogen electrophiles, these same hyperconjugative effects, acting between an intermediate epihalonium ion and a β C᎐X bond, have a very significant influence on the regiochemistry of the process. Where X is more electronegative than hydrogen then, provided that the β C᎐X bond bears a fixed periplanar relation to the epihalonium ion, anti-Markownikoff addition is strongly promoted to the extent that it becomes exclusive when two such β C᎐X bonds are present.…”
Section: Discussionmentioning
confidence: 77%
“…In comparing this aspect of the positive halogen additions to 1 and 2, we note that the behaviour is similar to that observed with diimide, which reacts stereospecifically exo with 5methylenedioxanes, but almost unselectively towards methylenecyclohexane. 1 For the reaction of diimide, this was most satisfactorily accounted for by invoking the pronounced difference in electrostatic potential field between the two faces of the double bond which calculations had shown for 1. This difference gives a substantial bias for exo (axial) attack by an electrophile with an appreciable dipole, which, with the exception of bromine, is the case for the electrophiles that we have examined here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations